(untitled) (Academic Journal of International University of Erbil, 2026)
Candida albicans is a common commensal of the human gastrointestinal tract (GIT) but can become an opportunistic pathogen under immunocompromised conditions. The ALS1 gene, part of the agglutinin-like sequence (ALS) family, encodes an adhesin that facilitates tissue attachment and biofilm formation, contributing significantly to C. albicans pathogenicity. This study aimed to determine the prevalence of C. albicans in clinical GIT samples and assess the presence of the ALS1 virulence gene among these isolates, using classical and molecular techniques. A total of 121 stool samples were collected from patients with GIT symptoms in Koya and Erbil City. Culturing was performed on Sabouraud Dextrose Agar and HiCrome™ for preliminary identification, followed by Gram staining, germ tube testing, and confirmation with the VITEK 2 ID system. Molecular detection of the 18S rRNA and ALS1 genes was conducted via colony PCR, and selected amplicons were verified by Sanger sequencing and BLAST alignment. Candida. albicans was isolated in 22.3% (27/121) of samples. Of these, 81.5% (22/27) tested positive for the ALS1 gene. PCR products were confirmed by sequencing, revealing high identity with reference strains in GenBank. Combining phenotypic and molecular assays ensured robust and accurate identification. The high prevalence of ALS1 among GIT-derived C. albicans isolates highlights its potential as a molecular marker for virulence and colonization risk.